Entrepreneurial Perspective on Customer Decisions to Watch Indonesian Movies - Djamaly, Muhammad Fadheel; Djumarno, Djumarno; Astini, Rina; Asih, Daru (Aptisi Transactions On Technopreneurship (ATT), 2025)
Customer Engagement reflects the extent of interaction between audiences and film products, serving as a key element within the movie industry. Various determinants such as lead actors, movie genres, movie ratings, and online reviews affect viewers intentions to watch films in theaters. This research investigates how customer engagement mediates the influence of these determinants on the intention to watch Indonesian films in cinemas. A quantitative research design was adopted, involving a survey of 315 respondents. The data were processed using the Structural Equation Modeling (SEM) technique with the SmartPLS program to assess the relationships among variables. The results indicate that lead actors, film genres, movie ratings, and online reviews significantly enhanced customer engagement. Customer engagement positively and significantly affected individuals decisions to watch Indonesian movies. It was also found to significantly mediate the effect of these variables on the decisions to wacth movies. This research contributes to relationship marketing theory by emphasizing the importance of customer engagement in developing strong and loyal consumer relationships. Additionally, it enriches consumer behavior literature by explaining the effect of customer engagement on the decisions to watch movies, offering practical implications for film marketers in formulating effective promotional and audience engagement strategies.